Reservoir space characterization of vuggy carbonate reservoirs with multiple scales: a case study of Ma 5-7 interval, Middle Ordovician Majiagou Formation, Daniudi area, Ordos Basin - Xiaoqi DING; Xin LIU; Zhuangzhuang QI; Wei ZHANG; Sihong LIU (Shiyou shiyan dizhi, 2021)
The reservoir space of carbonate rocks is of multiple scales and genesis mechanisms, and it is difficult to accurately demonstrate the reservoir space as well as physical properties.Millimeter-, micro- and nano-scale reservoir spaces were all developed in the Ma 5-7 interval (the 7th sub-member of the 5th member) of the Ordovician Majiagou Formation in Daniudi area, Ordos Basin. In order to study the storage space and physical properties, the storage space was characterized in layers at multiple scales, and combined with the approach of logging curves, a calculation model was established for the description of pores and caves.Several conclusions were made as follow. (1) For carbonate rock reservoirs with storage space of multiple scales, we can accurately describe their storage space by the means of core rubbing for dissolved pores (>1 mm), case thin section for intercrystalline pores (>2 μm), and argon ion polishing-scanning electron microscope for submicron and nano pores (< 2 μm). (2) On the basis of multi-scale reservoir space characterization, the acoustic porosity and neutron-density porosity can be constrained, and the corresponding intercrystalline pore porosity calculation model and dissolved pore porosity calculation model can be established, which have higher calculation accuracy.